2012
DOI: 10.3945/jn.111.155614
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Mucin 1 and Mucin 4 Inhibit Salmonella enterica Serovar Typhimurium Invasion of Human Intestinal Epithelial Cells In Vitro

Abstract: Salmonella infection is more frequent among infants than the general population, but the incidence is lower in breastfed babies. This study was to test whether human milk per se inhibited salmonella invasion of human intestinal epithelial cells in vitro, and to identify the milk components likely to be responsible for any inhibition. Salmonella typhimurium SL1344 invasion of FHs 74 Int and CaCo‐2 cells were the models of human intestinal epithelium infection. Internalization of FITC‐labeled salmonella into int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 35 publications
(35 reference statements)
0
43
0
Order By: Relevance
“…Sialic-acid glycans from MUC1 prevented attachment of S-fimbriated E. coli to buccal mucosal cells (184). Milk concentrations of MUC1 and MUC4 prevented invasion of Caco-2 by S. typhimurium , although the role of glycans in this phenomenon was not addressed (185). …”
Section: Milk Glycobiome Mediates Protection Against Infectious Diseasesmentioning
confidence: 99%
“…Sialic-acid glycans from MUC1 prevented attachment of S-fimbriated E. coli to buccal mucosal cells (184). Milk concentrations of MUC1 and MUC4 prevented invasion of Caco-2 by S. typhimurium , although the role of glycans in this phenomenon was not addressed (185). …”
Section: Milk Glycobiome Mediates Protection Against Infectious Diseasesmentioning
confidence: 99%
“…There are two types of mucins that has been the focus of research, MUC1 and MUC4 [32••]. A recent study showed that these mucins could inhibit Salmonella enterica serovar Typhimurium invasion of human epithelial cells in vitro [50]. Sialylated human milk mucin inhibited rotavirus replication in tissue culture and prevented rotavirus gastroenteritis in a mouse model; and blocked the adhesion of recombinant norovirus-like particles [32••].…”
Section: Protective Components Of Human Milkmentioning
confidence: 99%
“…Moreover, soluble factors contained in maternal milk also contribute to the protection of the neonates during breast feeding time and will be discussed later on. Of note, human milk contains mucin 1 and 4 which can bind pathogenic bacteria such as Salmonella Typhimurium and by competition with the host immune receptors, inhibit the invasion of epithelial cells [86]. Also, human milk oligosaccharides favor the selection of specific bacteria such as Bifidobacterium infantis which are able to consume them via mucus-utilization pathways, facilitating milk and solid food digestion [87].…”
Section: Adaptation Of the Gut Mucosa To Bacterial Colonizationmentioning
confidence: 99%